Pemanfaatan Sensor DS18B20 Sebagai Pemantau Suhu Air Untuk SPA Wellness Menggunakan Metode Fuzzy Mamdani - Yakuni, Ahmad; Islamiyah, Mufidatul (JURNAL SISTEM KOMPUTER ASIA, 2025)
This research discusses water temperature monitoring in wellness spas, using DS18B20 sensors, this research aims to improve the efficiency of water temperature management in wellness spas, ensure user comfort, and optimize energy resources. Fuzzy methods are used to handle temperature uncertainty and complexity, resulting in an adaptive and responsive temperature monitoring system. In the modeling of the system created, it produces an output in the form of an optimal temperature with a range of 37-40 Celsius, but if the sensor detects below that temperature, the system will loop to heat the water until the optimal temperature is reached. If the sensor detects the temperature at the normal threshold, the system will reduce the temperature according to the optimal temperature. In this study, the type of spa used is therapeutic. In modeling this system, the aim is to create an optimal environment for relaxation and well-being. With this approach, water temperature management can be customized according to individual preferences and environmental conditions, contributing positively to the user experience in the context of wellness spas. The research results indicate that the water temperature monitoring device using the DS18B20 sensor provides accurate results from testing with cold and hot water. Additionally, the heating element functions according to the desired set temperature, making it easy and efficient to determine each individual's temperature preference.